رۆڵى نه‌خشه‌سازى و ڕه‌نگدانه‌وه‌ى له‌پێگه‌ ئه‌لكترۆنیه‌ كوردییه‌كاندا رۆژنامه‌نوسانى پێگه‌ ئه‌لكترۆنیه‌كانى ناو شارى سلێمانى به‌نمونه‌ - أحمد, پ.ى. د. فوئاد عه‌لى; محمد, خوێندکار: سه‌ركه‌وت أحمد (Sulaimani Journal for Humanities, 2023)
This research under the title of "The role of design and its reflection in the Kurdish websites" has been done to achieve some goals, revealing the role of design in the websites and determining the level of importance of Kurdish websites to the design art, are among the most important objectives of this research. the researchers conducted descriptive research and used a survey method which is suitable with this research style, for collecting and obtaining data, the researchers used focus group interviews and survey form tool, in the focus group tool, experts in the field of design were interviewed in groups, and in the survey form, all the journalists of the websites in the city of Sulaymaniyah were included in a (comprehensive survey), the most important results this research has reached: design in websites has a significant role to reach media messages to the receivers, the Kurdish websites have not acted professionally with their website design, and they and have given little attention to it, implementing the principles of design in Kurdish websites is not at a good level.